"Celts" up and down the Alps. Insights on mobility patterns in the pre‐Roman/Celtic population from Verona (NE Italy, 3rd–1st c. BCE): A multi‐isotopic approach. Issue 3 (26th April 2022) - Laffranchi, Zita; Granados‐Torres, Arsenio; Lösch, Sandra; Zink, Albert; Dori, Irene; Delgado‐Huertas, Antonio; Milella, Marco
Abstract: Objectives: The Late Iron Age in continental Europe featured complex demographic processes including, among others, the establishment of transalpine "Celtic" communities on the Italian peninsula between the 4th and 1st centuries BCE. To date, only few data are available about mobility and migration in these populations. Here we explore these topics among the Cenomani of Seminario Vescovile (SV‐Verona, Italy, 3rd–1st c. BCE) through a multi‐isotopic approach and test the possible associations with sex, age and funerary treatment. Materials and methods: We analyzed isotopic ratios of oxygen ( δ 18 O) and carbon ( δ 13 C) from bone phosphate and collagen, respectively, of 49 individuals (23 males, 17 females, and 9 nonadults). In addition, we explored possible intraindividual lifetime changes by comparing collagen δ 13 C from bone and dentine of 26 individuals. We assessed nonlocality based on individual deviation of isotopic values from the population mean plus three times the median absolute deviation from the median (±3MAD). We then checked for isotopic differences between sexes and type of funerary treatment using Mann–Whitney tests. Results: One individual shows isotopic values consistent with a nonlocal origin. Five more individuals may have originated from a different locality. No statistical differences separate sexes and types of funerary treatment. Discussion: Results suggest a local origin of most of the individuals of SV with the few exceptions pointing especially to an Alpine origin. The low frequency of nonlocals at SV suggest a reduced mobility in this population, or the preeminence of short distance movements undetected by our analyses. Abstract :